Development of a Multiplex PCR Assay for Detection of Shiga Toxin-Producing Escherichia coli, Enterohemorrhagic E. coli, and Enteropathogenic E. coli Strains - Botkin, Douglas J.; Galli, Lucia; Sankarapani, Vinoth; Soler, Michael; Rivas, Marta; Torres, Alfredo G. (Frontiers in Cellular and Infection Microbiology, 2012)
Escherichia coli O157:H7 and other pathogenic E. coli strains are enteric pathogens associated with food safety threats and which remain a significant cause of morbidity and mortality worldwide. In the current study, we investigated whether enterohemorrhagic E. coli (EHEC), Shiga toxin-producing E. coli (STEC), and enteropathogenic E. coli (EPEC) strains can be rapidly and specifically differentiated with multiplex PCR (mPCR) utilizing selected biomarkers associated with each strain’s respective virulence genotype. Primers were designed to amplify multiple intimin (eae) and long polar fimbriae (lpfA) variants, the bundle-forming pilus gene bfpA, and the Shiga toxin-encoding genes stx1 and stx2. We demonstrated consistent amplification of genes specific to the prototype EHEC O157:H7 EDL933 (lpfA1-3, lpfA2-2, stx1, stx2, and eae-γ) and EPEC O127:H6 E2348/69 (eae-α, lpfA1-1, and bfpA) strains using the optimized mPCR protocol with purified genomic DNA (gDNA). A screen of gDNA from isolates in a diarrheagenic E. coli collection revealed that the mPCR assay was successful in predicting the correct pathotype of EPEC and EHEC clones grouped in the distinctive phylogenetic disease clusters EPEC1 and EHEC1, and was able to differentiate EHEC1 from EHEC2 clusters. The assay detection threshold was 2 × 104 CFU per PCR reaction for EHEC and EPEC. mPCR was also used to screen Argentinean clinical samples from hemolytic uremic syndrome and diarrheal patients, resulting in 91% sensitivity and 84% specificity when compared to established molecular diagnostic procedures. In conclusion, our mPCR methodology permitted differentiation of EPEC, STEC and EHEC strains from other pathogenic E. coli; therefore, the assay becomes an additional tool for rapid diagnosis of these organisms.